Description of the Spiritual and Psychological Well-Being Dimensions of Male and Female Nurses in Jayapura - Yoel, Sherly; Ranimpi, Yulius Yusak; Pilakoannu, Rama Tulus (Jurnal Keperawatan Respati Yogyakarta, 2020)
The two aspects of the basic needs of this research are spiritual and psychological well-being. Both aspects are considered more crucial because if viewed from the nurse’s job, a nurse (with a steady job) can already fulfill all three basic needs. This research was conducted in the General Hospital Jayapura, this study aims to describe the spiritual and psychological well-being aspects of male and female nurses in General Hospital Jayapura Papua. A descriptive qualitative method with a sample of 10 people was used in this research and the data was collected through observation and interview techniques. Data validation techniques were using triangulation and data analysis was using Miles and Huberman models. The results of this study were done on male and female nurses, found 6 categories following 2 groups of dimensions. The spiritual dimension are a relationship with God is the basis of life guidelines, working as a nurse is useful worship for many people, the meaning of life is a feeling of gratitude from oneself. The other dimension is psychological well-being: psychological health is a healthy soul, peaceful and able to know yourself, positive relationships are good relationships with others and self-acceptance as a nurse is a call of a life that is lived with a sense of responsibility.